Ornamental plants in Palu City, Central Sulawesi, Indonesia - MUHD. NUR SANGADJI; AMAR AKBAR ALI; AMILA FARWIZAH TIWATU; ZAHWA ARZETI BILBINA; REGITA CAHYANI; MUH. ARDIAN SATRIO NUGRAHA; PANJI ANOM RAMAWANGSA; FATHURRAHMAN FATHURRAHMAN; ZAINUDDIN BASRI; RAMADANIL PITOPANG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sangadji MN, Ali AA, Tiwatu AF, Bilbina ZA, Cahyani R, Nugraha MAS, Ramawangsa PA, Fathurrahman, Basri Z, Pitopang R. 2025. Ornamental Plants in Palu City, Central Sulawesi, Indonesia. Biodiversitas 26: 2576-2588. This research project investigating ornamental plant species in Palu City, Central Sulawesi, Indonesia, was conducted from May to September 2024. Furthermore, the main purpose was to document the diversity of ornamental plants in Palu City, Central Sulawesi, Indonesia. A botanical exploration strategy was used to observe and inventory ornamental plants in 8 districts directly. The collection and photography of all samples were conducted, followed by the identification at the Laboratory of Plant Biosystematics, Faculty of Sciences, and the Herbarium Celebense (CEB), Universitas Tadulako, Palu. Supplementary information, such as the local name, botanical name, family, and plant habitus (life form), was recorded, and then the labeled samples were deposited at CEB. The results showed a total of 264 species of ornamental plants distributed among 76 families, 197 genera, and 4 fern species, as well as 1 gymnosperm. The Euphorbiaceae family was the most extensively farmed, followed by the Arecaceae and Araceae families, with 18, 16, and 15 species, respectively. Among the 264 detected species of ornamental plants, three species were categorized under the vulnerable category of conservation status, including Adonidia merrillii palm (Arecaceae), Diospyros celebica (Ebenaceae), and Santalum album (Santalaceae). This research found that several ornamental plants were classified as Invasive Alien Plant Species (IAPS).